Error Rate and Ergodic Capacity of RF-FSO System with Partial Relay Selection in the Presence of Pointing Errors - Petkovic, Milica I; Imran Shafique Ansari; Djordjevic, Goran T; Qaraqe, Khalid A (arXiv.org, 2022)
This paper presents an analysis of a multiple dual-hop relaying system, which is composed of km-class radio frequency (RF)-free-space optical (FSO) links. Partial relay selection based on outdated channel state information (CSI) is employed in order to select active relay for further transmission. Amplify-and-forward relaying protocol is utilized. The RF links are assumed to be subject to Rayleigh fading, and the FSO links are influenced by both Gamma-Gamma atmospheric turbulence and pointing errors. On the basis of our previously derived expression for cumulative distribution function of the equivalent signal-to-noise ratio of the whole system, we derive novel analytical expressions for the average bit-error rate (BER) and ergodic capacity that are presented in terms of the Meijer's G-function and extended generalized bivariate Meijer's G-function, respectively. The numerical results are confirmed by Monte Carlo simulations. Considering the effect of time-correlation between outdated CSI and actual CSI related to the RF channel at the time of transmission, the average BER and the ergodic capacity dependence on various system and channel parameters are observed and discussed. The results illustrate that the temporal correlation between outdated and actual CSI has strong effect on system performance, particularly on BER values, when FSO hop is influenced by favorable conditions. Keywords: Bit error rate, ergodic capacity, free-space optical systems, partial relay selection, radio frequency systems.